Temperature dependent growth and inorganic ion composition of haemolymph of juvenile Sepia officinalis, 2006 - Wittmann, Astrid C (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2012)
B Body wet weight and mantle length of juvenile Sepia officinalis were monitored over a peroid of five weeks. The animals had hatched in our aquarium system in Bremerhaven, Germany at 16°C and were descendants of individuals collected in the Oosterschelde estuary, Netherlands. Animals were kept in natural sea water at 10 or 17°C and fed small live shrimp (Palaemonetes varians) ad libitum daily. At the end of the experiment some animals kept at 17°C were sacrificed using ethanol. Haemolymph was withdrawn from the head vein using syringe and needle. Haemolymph samples were stored at -20°C until Na+, Cl-, K+, Mg2+, Ca2+ and SO42- concentrations were determined using ion chromatography. Mean body weight more that tripled at 17°C during the investigation period, while growth was impared by exposue to 10°C. Haemolymph ion concentrations were similar to those in sea water, except for sulphate. The concentration of this ion in the haemolymph was more that ten times lower than in sea water.